PENERAPAN PENDEKATAN MODIFIED FREE INQUIRY SEBAGAI UPAYA MENINGKATKAN KREATIVITAS MAHASISWA CALON GURU DALAM MENGEMBANGKAN JENIS EKSPERIMEN DAN PEMAHAMAN TERHADAP MATERI FISIKA - Khanafiyah, S; Rusilowati, A (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M), Universitas Negeri Semarang, 2010)
This research aims to improve the creativity of students in developing experiments and the understanding of physics; especially wave; using application of modified free inquiry. This research is conducted in Physics Department, of Unnes. Questionnaire is used to measure creativity, observation sheet to measure the psychomotoric ability, while test sheets to measure the understanding of waves subject matter. Results were analyzed using a Likert scale. To test the effectiveness of modified free inquiry approach in enhancing studentsÃ¢â¬Å¸ creativity and students understanding of the wave subject matter, normalized gain formula is used. The results shows that by implementing modified free inquiry approaching in the learning process and allowing the students to apply their creativity, will remedy studentsÃ¢â¬Å¸ psychomotoric ability, increasing the number of the experiments type, enhancing students creativity and cognitive abilities. It is suggested that lecturer gradually and continously provides opportunity for learners to develop their creativity. Kata kunci : modified free inquiry, creativity